Comparison of three measures for insomnia in ischemic stroke patients: Pittsburgh sleep quality index, insomnia severity index, and Athens insomnia scale - Niu, Shuzhen; Wu, Qian; Ding, Silian; Wu, Lingchun; Wang, Li; Shi, Yan (Frontiers in Neurology, 2023)
Objective: This study investigated the consistency and determined the optimal threshold values of three scales in the assessment and diagnosis of insomnia of ischemic stroke (IS) patients. Methods: Participants in this study consisted of 569 acute IS patients. All 569 patients completed the assessment of the three insomnia scales. Insomnia of IS patients were assessed by Pittsburgh sleep quality index (PSQI), Insomnia Severity Index (ISI), and Athens insomnia scale (AIS). SPSS 23.0 statistical software was used to analyze the reliability Cronbach's alpha coefficients and consistency analysis Kappa values and to plot the receiver operating characteristic curve (ROC curve) of the three insomnia scales. Results: The PSQI and ISI questionnaires demonstrated high reliability with Cronbach's α coefficient values of 0.875 and 0.858, respectively, while the AIS questionnaire had an αcoefficient of 0.734, demonstrating acceptable reliability. The PSQI, ISI, and AIS questionnaires demonstrated “excellent” diagnostic ability with an AUC of 0.960 (95% CI: 0.946, 0.974), 0.911 (95% CI: 0.882, 0.941), and 0.876 (95% CI:0.837, 0.916), respectively. The best diagnostic cutoffs for PSQI, ISI, and AIS are ≥9, ≥15, and ≥8, respectively. Conclusions: Each of the three questionnaires has advantages and disadvantages when assessing insomnia. In the evaluation of insomnia in IS patients, the best questionnaire selection should be made according to the purpose of clinical evaluation and considering the sensitivity and specificity of the questionnaire.